Obesity and the levels of liver enzymes (ALT, AST & GGT) in East Medinipur, India - Das, Ajay Kumar; Chandra, Prasanna; Gupta, Akash; Ahmad, Naved (Asian Journal of Medical Sciences, 2014)
Objective Obesity is a common disorder in our country. Most widely used method to gauge obesity is Body Mass Index (BMI) which is equal to weight in kilogram divided by height in meter square. The objective of our study was to find the levels of liver enzymes ALT, AST & GGT in two groups (overweight individuals and obese individuals). Methods: A total no of 156 individuals were selected for the study and they were categorized into three groups on the basis of BMI- Group I Normal, BMI 18.5 to 24.9 (n=72), Group II Overweight, BMI 25.0 to 29.9 (n=39) and Group III Obese, BMI >30 (n=45). Serum ALT, AST & GGT were estimated by Accurex AC 112 plus semi auto analyser and values were given in U/L. Results: Values of ALT, AST & GGT were with in the normal references range in all the three groups. Conclusion: No significant relation was found between ALT, AST & GGT in normal, overweight and obese individuals. DOI: http://dx.doi.org/10.3126/ajms.v6i1.10147 Asian Journal of Medical Sciences Vol.6(1) 2015 40-42